(untitled) (Praxis Educativa, 2026)
The article analyses a dialogue on the challenges of contemporary art education with IA·MAE, an artificial intelligence prototype configured as a digital avatar of Ana Mae Barbosa and developed within the EDARCLUSIÓN research project. From a qualitative and interpretive approach, the study combines content analysis and critical discourse analysis to examine how the system reorganises notions linked to critical art/education, postdigitality, algorithmic culture, artificial intelligence and teacher education. The results are grouped into four categories: postdigital art education as a critical and situated practice; algorithmic culture and the risk of homogenisation; AI as an ambivalent mediation; and teacher education as a continuous process of critical reflection. The study concludes that IA·MAE neither replaces Barbosa nor acts as an oracle, but rather operates as a technocultural device useful for thinking with and about AI, revealing both pedagogical possibilities and structural limits of generative systems.